Impact of Social Networking Sites in Scholarly Communication by State Universities of Uttrakhand - Nigam, Karnika; Singh, M.P. (DESIDOC Journal of Library & Information Technology, 2016)
This study finds out usage pattern of social networking sites (SNS) of academicians in scholarly communication in the Central Himalayan region of Uttarakhand state universities of India. The results revealed that 93 % faculty members of State universities of Uttarakhand were using SNS and sharing of information was the highest amongst them. 44 % were using SNS several times a day, 48 % faculty members thought that SNS information were reliable. 33 % faculty members believed that there was a possibility of fraud through SNS and 41.64 % faculty members believed that SNS had a little impact on their lives. 28.75% were using Facebook, which was highest in all SNS. The result indicated that the percentage usage by the faculty members in terms of the latest knowledge was 38.0%. Mostly faculty members were using the SNS from their homes. One very important factor responsible for this could be the lack of Wi-Fi facility available to them in all the campuses of the universities. Therefore the study recommends that Wi-Fi should be made available in all the universities, so that the faculties can use them in their academic pursuit, during their working hour in the campus, and this will further lead to an in depth use of SNS for academic excellence.